2015
DOI: 10.1002/joc.4435
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and changes in cloud cover in the area of the Black, Caspian, and Aral seas (1991–2010): a comparison of surface observations with satellite and reanalysis products

Abstract: This article presents a climatology of total cloud cover (TCC) in the area of the three inland Eurasian seas (Black, Caspian, and Aral Sea). Analyses are performed on the basis of 20 years of data (1991–2010), collected from almost 200 ground stations. Average TCC is 49%, with broad spatial and seasonal variability: minimum TCC values are found in summer and to the southeast, whereas maximum values correspond to winter and to the northwest. For the whole area, linear trend analyses show that TCC did not vary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 81 publications
2
9
0
Order By: Relevance
“…Even if all databases emphasize the decline of clouds in the Mediterranean during the last decades, the disagreement in rate and significance of the trends highlights the uncertainties of the different satellite and reanalysis products in capturing trends of clouds, in agreement with other recent studies over other regions 33 38 , even if the latter products can reproduce observed TCC trends in US 39 .…”
Section: Can We Trust Satellite and Reanalysis Cloud Products Over Thsupporting
confidence: 83%
“…Even if all databases emphasize the decline of clouds in the Mediterranean during the last decades, the disagreement in rate and significance of the trends highlights the uncertainties of the different satellite and reanalysis products in capturing trends of clouds, in agreement with other recent studies over other regions 33 38 , even if the latter products can reproduce observed TCC trends in US 39 .…”
Section: Can We Trust Satellite and Reanalysis Cloud Products Over Thsupporting
confidence: 83%
“…3), from November to April the decadal difference of the DTR was negative (-0.37 C dec À1 in FMA) and positive during the rest of the year (>0.20 C dec À1 ). The negative value of the decadal DTR difference in spring is consistent with the positive trend of the total cloud cover identified in this region, which is associated with intensification of the activity of the South-Caspian, Murgab and Upper Amu Darya cyclones (Calb o et al, 2016). On the other hand, as observed in Fig.…”
Section: Summary and Discussionsupporting
confidence: 87%
“…Details of how to convert the native, continuous cloud fraction (0–100%) into discrete okta values (0–8) are given in the WMO's manual on coding the results of meteorological observations [SYNOP FM‐12 code; WMO ()]. However, there are no guidelines for the reverse conversion from the okta to the continuous scale and climatologists usually assume that 1 okta equals 12.5% (Meerkötter et al, ; Matuszko, ; Sanchez‐Lorenzo and Wild, ; Calbó et al, ), and the usage of other weights is exceptionally rare (Boers et al . ()).…”
Section: Introductionmentioning
confidence: 99%